2022
DOI: 10.1007/s00374-022-01671-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen isotope enrichment predicts growth response of Pinus radiata in New Zealand to nitrogen fertiliser addition

Abstract: The fertiliser growth response of planted forests can vary due to differences in site-specific factors like climate and soil fertility. We identified when forest stands responded to a standard, single application of nitrogen (N) fertiliser and employed a machine learning random forest model to test the use of natural abundance stable isotopic N (δ15N) to predict site response. Pinus radiata growth response was calculated as the change in periodic annual increment of basal area (PAI BA) from replicated control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Secondly, we utilized the random forest method to determine the relative im portance of regulating biotic and abiotic factors on Ra and Rh. This powerful machine learning technique is robust to multicollinearity and overfitting [36]. This study ran 100 times with evaluation based on the increased mean square error (lnMSE).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we utilized the random forest method to determine the relative im portance of regulating biotic and abiotic factors on Ra and Rh. This powerful machine learning technique is robust to multicollinearity and overfitting [36]. This study ran 100 times with evaluation based on the increased mean square error (lnMSE).…”
Section: Discussionmentioning
confidence: 99%
“…Though N processes and N 2 O emission were quite variables with the treatments, saltwater tended to enhance N mineralization and thus loss of N, indicating that saltwater incursion into freshwater wetlands might reduce the N sink capacity of the coastal wetlands. In forests, Garrett et al (2023) showed that the δ 15 N can be used as an indicator of N availability status and thus as a predictor of site productivity responses to N fertilizer in New Zealand. Though the δ 15 N has been widely used to estimate the degree of N saturation of forests, this study is unique as it extended the use of δ 15 N in predicting forest responses to N fertilization.…”
mentioning
confidence: 99%